Interactions Between Microplastics and Heavy Metals in Aquatic Environments: A Review - Liu, Sitong; Shi, Jiafu; Wang, Jiao; Dai, Yexin; Li, Hongyu; Li, Jiayao; Liu, Xianhua; Chen, Xiaochen; Wang, Zhiyun; Zhang, Pingping (Frontiers in Microbiology, 2021)
Microplastics (MPs), tiny particles broken down from larger pieces of plastics, have accumulated everywhere on the earth. As an inert carbon stream in aquatic environment, they have been reported as carriers for heavy metals, and exhibit diverse interactive effects. However, these interactions are still poorly understood, especially mechanisms driving these interactions and how they pose risks on living organisms. In this mini review, a bibliometric analysis in this field was conducted, and the mechanisms driving these interactions were examined. Furthermore, the combined toxic effects and the potential hazards to human health were discussed. Finally, the future research directions in this field were suggested. This review summarized the recent research progress in this field, and highlighted the microbe’s important roles on the interactions between MPs and heavy metals.